Charges to be Declined: Legal Challenges and Policy Debates Surrounding Non-Prosecution Initiatives in Massachusetts - Foster, John E. (2019)
The election of “progressive prosecutors” introduces new objectives and tools into the traditional “tough on crime” playbook of local prosecution. Newly-elected District Attorney Rachael Rollins of Suffolk County, Massachusetts has proposed one such tool: non-prosecution of certain criminal laws, chiefly non-violent misdemeanors. This Note explores the likelihood of success of legal challenges to categorical non-prosecution, primarily whether non-prosecution unconstitutionally violates the separation of powers. This Note considers whether non-prosecution implicates the rights of victims and notions of justice as a public or private domain. It also analyzes the merits of non-prosecution as a policy. Some critics challenge the ability of progressive prosecutors to change the criminal justice system from the inside, while others claim that non-prosecution of so-called quality-of-life crimes damages communities rather than enriching them. Alternatively, those supportive of reform herald non-prosecution as a means of allowing local communities to influence the conduct of law enforcement, arguing that petty crime reflects public health failures that should be resolved by social services instead of jail-time. As novel as it is controversial, the proposed non-prosecution policy deserves close attention from legal scholars and criminal reform advocates